CENTRAL BANK DIGITAL CURRENCIES: ECONOMIC DRIVERS AND IMPLICATIONS - Khaleel Ismael Azeez; Omar Abdulla Mohammad; Anas Dheyab Salim (American Journals, 2023)
In light of the development of new technologies in the banking and financial industries, the general trend is to move towards a non-monetary society, which is taken for granted in the economies through the central banks' recognition of the importance of the digital currency. Where many central banks in developed countries are de-signing their own version of the digital currency and the mechanism and scenarios for its issuance. As the success of any digital currency depends on its competitiveness in the market, within a few years central banks have stepped up their efforts in the research and development of central bank digi-tal currencies (CBDCs). However, central bank digital currencies should be considered in the full context of the digital economy and data centraliza-tion, which raises concerns about competition, payment system integrity, and privacy. This paper provides a general idea of (CBDCs) and microeco-nomic considerations related to operational and technological structures, privacy, and macroeco-nomic effects on the financial system, general sta-bility, and monetary policy.
Keywords: Money, Central bank digital currencies, Central banks Encrypted currencies.